Hypermentalizing in Social Anxiety: Evidence for a Context-Dependent Relationship - Ballespí, Sergi; Vives, Jaume; Sharp, Carla; Tobar, Andrea; Barrantes-Vidal, Neus (Frontiers in Psychology, 2019)
Social anxiety means fear of scrutiny and of others’ negative evaluation, thus indicating that hypermentalizing (i.e., the over-attribution of intentions and thoughts to others) might be the most common error of social cognition in social anxiety. However, evidence for this is weak. One explanation is that hypermentalizing is not stable in social anxiety, but rather context-dependent. The first aim of the current study was testing this hypothesis. The second aim was analyzing whether the association between social anxiety and hypermentalizing is moderated by a negative self-image. One-hundred and thirteen young adults (85.8% females; M=21.1 years old; SD=2.7) were assessed on measures of social anxiety, hypermentalizing, and self-image. Results revealed that hypermentalizing is associated with social anxiety only in the self-referential social situation (B= 2.68 [95% CI: 0.72 – 4.65], p= 0.007). This supports that hypermentalizing is not global in social anxiety (i.e., a stable cognitive style), but rather is active only in some contexts. Implications for the conceptualization and treatment of social anxiety are discussed. Contrary to predictions, neither self-esteem, nor positive or negative self-schema moderated the association between social anxiety and self-referential hypermentalizing. This contradicts findings in the field of paranoid delusion and requires replication, including measures of implicit self-esteem.